The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7759/cureus.12653
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Association Between Psoriasis and Thyroid Diseases

Abstract: Psoriasis is a chronic relapsing/remitting autoimmune disease affecting skin and fingernails. It is associated with many other autoimmune diseases such as rheumatoid arthritis, celiac disease, Crohn's disease, and thyroid diseases. Two important autoimmune thyroid diseases-Hashimoto's thyroiditis (hypothyroidism) and Grave's disease (hyperthyroidism)-affect the body's significant organs such as the brain, muscles, digestive function, and the skin. Although some studies have established the connection between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 43 publications
0
4
0
4
Order By: Relevance
“…Previous research suggests that there are several commonalities in the pathophysiology shared between psoriasis and Graves' disease, such as hormones, genetic factors and oxidative stress. 5 Therefore, when the current patient showed poor responses to a variety of treatments, including conventional therapies, Janus kinase inhibitor inhibitors and biologics, her medical team speculated that this was related to the underlying Graves' disease, so she underwent iodine-131 treatment at same time. Finally, her treatment was switched to the IL-23 inhibitor, guselkumab, which resulted in the resolution of her psoriatic lesions.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous research suggests that there are several commonalities in the pathophysiology shared between psoriasis and Graves' disease, such as hormones, genetic factors and oxidative stress. 5 Therefore, when the current patient showed poor responses to a variety of treatments, including conventional therapies, Janus kinase inhibitor inhibitors and biologics, her medical team speculated that this was related to the underlying Graves' disease, so she underwent iodine-131 treatment at same time. Finally, her treatment was switched to the IL-23 inhibitor, guselkumab, which resulted in the resolution of her psoriatic lesions.…”
Section: Discussionmentioning
confidence: 98%
“…2,3 Autoimmune thyroid disease is considered to be closely related to psoriasis, because free thyroxine is increased significantly in psoriatic patients and patients with thyroiditis have more extended disease periods; 4 and in severe psoriasis, there are increased levels of thyroid-stimulating hormone (TSH). 5 Previous studies have demonstrated a link between psoriasis and thyroid illness as well as the involvement of type 1 helper T (Th1) cell cytokines in the pathogenesis of both psoriasis and Graves' disease, which is the most common cause of hyperthyroidism in iodine-replete areas. 5 A previous study indicated that methimazole, the first-line treatment for hyperthyroidism, could alleviate psoriasis through a variety of pathways by lowering the psoriasis area and severity index (PASI) scores of the patients after 6-8 weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetinis polinkis yra reikšmingas psoriazės patogenezėje, tačiau aplinkos veiksniai gali suaktyvinti ligą. Psoriazė yra susijusi su įvairiomis ligomis, įskaitant metabolinį sindromą, cukrinį diabetą, širdies ir kraujagyslių ligas, kitas uždegimines autoimunines ligas, pvz., reumatoidinį artritą, celiakiją, Krono ligą [9]. Daugelis perspektyvinių ir retrospektyvių tyrimų esant skirtingam tiriamųjų skaičiui parodė reikšmingą teigiamą psoriazės ir Hašimoto tiroidito ryšį, kurį patvirtintų: klinikiniai ypatumai (pasireiškimas odoje): pacientams, sergantiems Hašimoto tiroiditu ir kitomis skydliaukės ligomis, dažnai pastebima daugybė odos apraiškų.…”
unclassified
“…Daugelis perspektyvinių ir retrospektyvių tyrimų esant skirtingam tiriamųjų skaičiui parodė reikšmingą teigiamą psoriazės ir Hašimoto tiroidito ryšį, kurį patvirtintų: klinikiniai ypatumai (pasireiškimas odoje): pacientams, sergantiems Hašimoto tiroiditu ir kitomis skydliaukės ligomis, dažnai pastebima daugybė odos apraiškų. Pavyzdžiui, pacientams, sergantiems psoriaze ir itin sunkiu hipotiroidizmu, buvo pastebėtas reikšmingas odos pažeidimų pagerėjimas normalizavus tiroksino kiekį organizme [9];• keletas patofiziologinių mechanizmų, bendrų psoriazei ir skydliaukės ligoms. Vieną iš svarbiausių vaidmenų atlieka hormonai: skydliaukės hormonai ir jų receptoriai, esantys odoje, yra būtini skatinti odos proliferaciją, veikdami kaip endogeniniai odos uždegimo inhibitoriai bei didindami epidermio augimo veiksnio kiekį (skatina keratinocitų proliferaciją ir diferenciaciją).…”
unclassified